Mapping the Invisible : The Informal Food Economy of Cape Town, South Africa - Battersby, Jane (Jane Elizabeth), 1975-; Mngqibisa, Ncedo; Marshak, Maya (Urban food security series, 2016)
This report argues that it is essential to understand the dynamics of the informal food retail sector because of its vital role in ensuring greater access to food by the urban poor. Existing policy frameworks to address food security and to govern the informal sector tend to neglect informal retail in the food system. As a result, the sector is poorly understood. The report therefore attempts to identify the characteristics of the sector that impact on its ability to address the food needs of the neighbourhoods in which the businesses are located. Although the research is focused on Cape Town, the findings are of broader relevance.